Synthesis and characterization of block poly(ester‐ether‐urethane)s from bacterial poly(3‐hydroxybutyrate) oligomers. Issue 11 (15th March 2017) - Debuissy, Thibaud; Pollet, Eric; Avérous, Luc
ABSTRACT: Telechelic hydroxylated poly(3‐hydroxybutyrate) (PHB‐diol) oligomers have been successfully synthesized in 90–95% yield from high molar mass PHB by tin‐catalyzed alcoholysis with different diols (mainly 1, 4‐butanediol) in diglyme. The PHB‐diol oligomers structure was studied by nuclear magnetic resonance, Fourier transformed infrared spectroscopy MALDI‐ToF MS, and size exclusion chromatography, whereas their crystalline structures, thermal properties and thermal stability were analyzed by wide angle X‐ray scattering, DSC, and thermogravimetric analyses. The kinetic of the alcoholysis was studied and the influence of (i) the catalyst amount, (ii) the diol amount, (iii) the reaction temperature, and (iv) the diol chain length on the molar mass was discussed. The influence of the PHB‐diol molar mass on the thermal stability, the thermal properties and optical properties was investigated. Then, tin‐catalyzed poly(ester‐ether‐urethane)s (PEEU) of M n = 15, 000–20, 000 g/mol were synthesized in 1, 2‐dichloroethane from PHB‐diol oligomers ( P ester ) with modified 4, 4'‐MDI and different polyether‐diols ( P ether ) (PEG‐2000, PEG‐4000, and PPG‐PEG‐PPG). The influence of the PHB‐diol chain length, the P ether / P ester ratio, the polyether segment nature and the PEG chain length on the thermal properties and crystalline structures of PEEUs was particularly discussed. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 1949–1961 Abstract : The kinetic of the synthesis of PHB‐diol oligomers by tin‐catalyzed PHB alcoholysis was first studied. Then, synthesis of HB‐based poly(ester‐ether‐urethane)s copolymers from PHB‐diol, PPG‐PEG‐PPG‐diol or PEG‐diol and 4, 4'‐MDI was performed in solution. Synthesized products exhibited a good thermal stability without degradation below 200 °C, as well as tunable thermal properties and crystalline structures according to the diol segment chain length and the HB content.